2023
DOI: 10.1093/neuonc/noad073.168
|View full text |Cite
|
Sign up to set email alerts
|

HGG-19. Clinical Response to the Pdgfra/Kit Inhibitor Avapritinib in Pediatric and Young Adult High-Grade Glioma Patients With H3k27m or Pdgfra Genomic Alterations

Abstract: PDGFRA is commonly altered in pediatric and young adult high-grade gliomas (pHGGs) including histone 3 lysine 27-mutated diffuse midline gliomas (H3K27M DMG), a fatal disease with no current options for cure. We performed comprehensive genomic and transcriptomic analyses of n=259 pediatric high-grade glioma cases which revealed PDGFRA genomic alterations in ~15% of patients. H3K27M DMGs had significantly higher PDGFRA expression compared to H3 wild-type tumors regardless of genomic alteration. Tumors with PDGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…PDGFRA amplifications were predominantly observed within the DIPG subset (62%) while PDGFRA mutations were conversely found more often within hemispheric GBMs (54%) (204). A recent study revealed 15% of pHGGs to be harboring PDGFRA alterations, of which H3K27M DMGs exhibited significantly higher levels of PDGFRA, highlighting a targetable locus (205). Another study has shown that 50% of hemispheric H3.3G34R/V mutations harbor a PDGFRA mutation (201).…”
Section: Receptor Tyrosine Kinase Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…PDGFRA amplifications were predominantly observed within the DIPG subset (62%) while PDGFRA mutations were conversely found more often within hemispheric GBMs (54%) (204). A recent study revealed 15% of pHGGs to be harboring PDGFRA alterations, of which H3K27M DMGs exhibited significantly higher levels of PDGFRA, highlighting a targetable locus (205). Another study has shown that 50% of hemispheric H3.3G34R/V mutations harbor a PDGFRA mutation (201).…”
Section: Receptor Tyrosine Kinase Pathwaysmentioning
confidence: 99%
“…As a result, combinatorial therapy in conjunction with PDGFRA inhibition may offer a more viable solution for tumor regression. Avapritinib, a BBB penetrating PDGFR inhibitor, is currently being investigated as a potential therapeutic against PDGFRA mutant pHGG and has shown favorable toxicity profiles (205)(206)(207)(208). Adult GBM cell lines of the proneural subtype have shown sensitivity to PDGFRA inhibition (209).…”
Section: Receptor Tyrosine Kinase Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation